Reproductive cycle and sperm storage of female coral snakes, Micrurus corallinus and Micrurus frontalis - Bassi, Erick Augusto [UNESP]; Coeti, Rafaela Zani; Almeida-Santos, Selma Maria De [UNESP] (Brill Academic Publishers, 2020)
We analyzed the hypothesis that the lack of synchronization between the mating and ovulation period of Micrurus frontalis (BRT clade) is indicative of the capacity of females to store sperm. Conversely, since these reproductive events occur in the same season for Micrurus corallinus (BRM clade), sperm storage is not expected. Thus, we analyzed the reproductive cycle of female M. corallinus and M. frontalis, and investigated the occurrence of sperm storage. Our results showed that these two species of coral snakes (clades BRM and BRT) possess different reproductive cycles. Micrurus frontalis exhibits an extensive reproductive period encompassing three seasons (summer, autumn and winter), while M. corallinus directs secondary vitellogenesis and ovulation to the hottest period of the year (spring and summer). We confirm, for the first time, the strategy of sperm storage (SSr) in females of the genus Micrurus. We observed sperm storage receptacles located in the non-glandular uterus in all seasons of the year for M. corallinus and in spring, summer and autumn in M. frontalis. Furthermore, the presence of SSr in females in the non-reproductive (post-ovulatory) period, the verification of myoid cells around the receptacles and secretion of neutral carbohydrates in the lumina of SSrs may indicates a long-term storage. The posterior infundibulum is another possible region of sperm storage by the presence of tubular ciliated gland; however, reproductive studies with other species of the genus are necessary for a better understanding of the reproductive strategies of the BRT and BRM clades.
Keywords: Elapidae; long-term storage; Micrurus; reproduction